A strong convergence of modified subgradient extragradient method for solving bilevel pseudomonotone variational inequality problems. (2nd June 2020) - Viet Thong, Duong; Van Hieu, Dang
ABSTRACT: In this work, we investigate a new extragradient method for finding an element of the set of solutions of the bilevel pseudomonotone variational inequality problem in real Hilbert spaces. We only use one projection to construct the algorithm and the strong convergence theorem proved under suitable conditions. Numerical experiments illustrate the performances of our new algorithm and present a comparison with related algorithms.